Synthesis and biological potency of anilino‐triazine insecticides. Issue 10 (6th June 2017) - Johnson, Timothy C; Brown, Annette V; Bryan, Kristy K; Guenthenspberger, Katherine K; Hunter, Ricky; Martin, Timothy P; Niyaz, Noormohamed; Tisdell, Gene F; Trullinger, Tony
Abstract: BACKGROUND: An insecticide screening effort identified N ‐(4‐bromophenyl)‐4, 6‐bis(2, 2, 2‐trifluoroethoxy)‐1, 3, 5‐triazine‐2‐amine as having weak potency against two lepidopteran species, Helicoverpa zea and Spodoptera exigua . A structure–activity relationship study about the trifluoroethoxy substituents and the aniline of this compound was carried out in an effort to improve insecticidal potency. RESULTS: Initially, a series of analogs bearing various substituents on the aniline were prepared, and the insecticidal potency was evaluated against H. zea and S. exigua in greenhouse diet feeding assays. The results showed that electron‐withdrawing substituents, such as Cl, Br and CF3, were preferred over electron‐donating substituents, such as methoxy, and that potency was significantly better when the substituent was in the para ‐position. Additional investigations showed that bis(anilino)trifluoroethoxytriazines were more potent. Replacement of the remaining trifluoroethyl group in the bis(anilino)triazine series with an alkyl amine lead to compounds of equal or superior efficacy. CONCLUSION: The work presented showed that electron‐withdrawing substituents in the para ‐position of the aniline ring of the initial hit delivered the best levels of insecticidal potency against the two insect species tested. Further investigations showed that potency could be improved by replacing one of the two trifluoroethoxy groups with additional 4‐substituted aniline. This level of potency was maintained or further improved when the remaining trifluoroethoxy was replaced with a substituted amine. © 2017 Society of Chemical Industry